Can newborn infants safely be discharged at lower weights from hospital care - Mokhachane, Mantoa (My University, 2014)
At the neonatal unit at Baragwanath Hospital, 22% of aM admissions weighed less than 1500g at birth at the time of the study. This group of babies are responsible for a formidable part of both the workload and' expenditure of any neonatal unit The earlier discharge of these babies offers significant advantages to both parents and the health service,